A Review of Design Considerations of Centrifugal Pump Capability for Handling Inlet Gas-Liquid Two-Phase Flows - Qifeng Jiang; Yaguang Heng; Xiaobing Liu; Weibin Zhang; Gérard Bois; Qiaorui Si (Energies, 2019)
Most of the pumps working under two phase flows conditions are used in petroleum industry applications, like electrical submersible pumps (ESP) for hydrocarbon fluids, in chemistry, nuclear industries and in agriculture for irrigation purposes as well. Two-phase flows always deteriorate overall pump performances compared with single flow conditions. Several papers have been published aiming to understand flow physics and to model all the main mechanisms that govern gas pocket formation and surging phenomena. These mechanisms depend on the pump type, the impeller geometry, the rotational speed, design and off-design liquid flow rate conditions, the volumetric gas fraction, the fluid properties and the inlet pressure. In the present paper, a review on two phase performances from various centrifugal pumps designs is presented, mainly based on experimental results. The main focus is devoted to detect the significant geometrical parameters that: (1) Modify the pump head degradation level under bubbly flow regime assumption; (2) Allow single stage centrifugal pumps keep working under two-phase flow conditions with high inlet void fraction values before pump shut down, whatever the pump performance degradations and liquid production rates should be. Because most of the published experimental studies are performed on dedicated laboratory centrifugal pump models, most of the present review is based on air-water mixtures as the working fluid with inlet pressures close to atmospheric conditions. The following review supposes that gas phase is considered as a non-condensable perfect gas, while the liquid phase is incompressible. Both phases are isolated from external conditions: neither mass nor heat transfer take place between the phases.